The Stability Analysis of the Lusi Mud Volcano Embankment Dams using FEM with a Special Reference to the Dam Point P10.D - Agustawijaya, D.S.; Sukandi . (Civil Engineering Dimension, 2012)
Since the eruption of the Lusi Mud volcano in Sidoarjo, East Java, on May 2006, soil embankment dams have been built to keep hot mud within the ponds. Unfortunately, since the dams were sitting on poor weak ground, land subsidence intensively occurred around the dams. A finite element method (FEM) was, then, applied to evaluate the stability of the dams particularly of the dam point P10.D, being considered as the most unstable point over 29 other dam points. Results show that the dam displacements in vertical and horizontal directions were high. The total displacements of the final design were about 1.5 m in both static- and dynamic-state conditions. These modelled data show a similar trend with field measurement data. The dam had only a factor of safety of about 1.1, and the dam might fail through a deep slide mode.